Can lies be detected unconsciously? - Moi, Wen Ying; Shanks, David R. (Frontiers in Psychology, 2015)
People are typically poor at telling apart truthful and deceptive statements. Based on the Unconscious Thought Theory, it has been suggested that poor lie detection arises from the intrinsic limitations of conscious thinking and can be improved by facilitating the contribution of unconscious thought (UT). In support of this hypothesis, Reinhard et al. (2013) observed improved lie detection among participants engaging in UT. The present study aimed to replicate this UT advantage using a similar experimental procedure but with an important improvement in a key control condition. Specifically, participants judged the truthfulness of eight video recordings in three thinking modes: immediately after watching them or after a period of unconscious or conscious deliberation. Results from two experiments (combined N = 226) failed to reveal a significant difference in lie detection accuracy between the thinking modes, even after efforts were made to facilitate the occurrence of an UT advantage in Experiment 2. The results imply that the UT advantage in deception detection is not a robust phenomenon.